Ð˜Ð·ÑƒÑ‡ÐµÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾Ñ‡ÑƒÐ²ÑÑ‚Ð²Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ð¾ÑÑ‚Ð¸ Ð¼ÐµÐ·ÐµÐ½Ñ…Ð¸Ð¼Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÑÑ‚Ñ€Ð¾Ð¼Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº Ð² ÑÐ¾ÑÑ‚Ð°Ð²Ðµ Ð°Ð»ÑŒÐ³Ð¸Ð½Ð°Ñ‚Ð½Ñ‹Ñ… Ð¼Ð¸ÐºÑ€Ð¾ÑÑ„ÐµÑ€ - Pravdyuk, A. I.; Petrenko, Yu. A.; Kholodnyy, V. S.; Grischuk, V. P.; Petrenko, A. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
Three-dimensional culture of mesenchymal stromal cells (MSC), encapsulated in alginate microbeads is a perspective direction of cell biology and tissue engineering, indicating the need of the development of their low temperature preservation methods. The study describes the possibility of cryopreservation of MSC within alginate microbeads by slow cooling under protection of DMSO. Comparison study of MSC within alginate microbeads and as non-encapsulated cell suspension during cryopreservation under protection of 10% DMSO did not show significant differences in cells’ cryosensitivity, while during cryopreservation with 5% DMSO encapsulated MSC had lower viability values. Survival and metabolic activity of MSC after cryopreservation within alginate microbeads depended on DMSO concentration in cryoprotective medium and rised with increase of DMSO concentration from 5% to 10%. Initiation of crystallization during slow program cooling under protection of 10% DMSO allowed to achieve maximal values of survival and metabolic activity of encapsulated cells. The results of this study could be used for the banking of MSC encapsulated into alginate microbeads.